(untitled) (International Journal of Engineering and Computer Science, 2016)
The best answers to the fuel crises compelled to survive made a sustainable road transportation. One such effort in this regard is reported in this paper. Due to overcome of power electronics, the population of hybrid vehicle is also hiking up day by day. The Brushless DC motor is considered as potential drive to automotive applications such as the (Hybrid vehicles). Design of a direct drive, Brush less DC motor is employed (BLDC) or (electronically commutated motors). Many constraints have been considered, such as the size of the motor, maximum driving current and maximum output power. The diameter and the stack length are limited by using modern analytical tools of the prototype vehicle. Nobel analytical tools are used to obtain static and dynamic characteristics of the motor and geometrical verifications for low cost efficient design. A low cost electronic controller compatible for present application has been developed and designed in this paper. The prototype is fabricated and tested on a light weight electric vehicle such as the car and two wheeler. This automotive model’s performance was tested and its results are simulated in this paper. It has lot of advantages such as the generating power by regenerative braking at speed barkers, recharging the battery while the vehicle is in under the motion.